Syarat dan Ketentuan Menjadi Warga Muhammadiyah Yang Berakhlak Sesuai Al-Qur'an Dan As-Sunnah - Iwan Maulana; Mhd Rizki; Mustafain Rambey (Jurnal Ilmiah Wahana Pendidikan, 2022)
Requirements to become Muhammadiyah citizens in Muhammadiyah learning for students of Muhammadiyah University of North Sumatera, Islamic Education study program, Faculty of Islamic Religion, Muhammadiyah University of North Sumatera. This research is a requirement to be a Muhammadiyah member. This type of research is Qyalitative Research. Data collection techniques used include observation, interviews and docementation. The data analysis techniques is by reducing data, presenting data and verifying and making conclusion. The results of this study indicate that the requirements for becoming Muhammadiyah members in our environment are still uneven. The obstacle faced in becoming Muhammadiyah members is the lack of understanding of same residents about Muhammadiyah values